The 1991 Political Constitution and the Social rights, alternatives to overcome poverty in Colombia - Estupiñán, Joan Miguel Tejedor (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The article describes in the first place the economic, social and cultural rights recognized in Colombia since the Constitution of  1991 and its relationship to poverty in Colombia, in a second step, describes the situation of these rights from the indicators for poverty study, as the index of Unsatisfied Basic Needs (NBI), the poverty Line (LP), the Human Development Index (HDI), among others, third, there is a critical analysis of this situation through alternative reports to the national government reports, finally conclusions are presented for analysis and generation of public policies to development and protection of ESC rights in Colombia.